Exigências de lisina para mantença de codornas de corte determinadas por diferentes técnicas - OLIVEIRA, Francisco Loiola de (2021)
The meat quail raise (Coturnix coturnix coturnix) has shown significant growth in recent years, being an interesting option for the diversification of poultry production. However, knowledge about the nutritional requirements of these birds is still scarce. In the nutritional field, lysine (Lys), an amino acid directed almost exclusively to protein deposition, is used as a reference in establishing the requirements of other amino acids. Lys maintenance requirement in broilers have been studied for decades, both by the total excreta collection technique and by the comparative slaughter technique, been important direct the study of this theme to the quail. Thus, the aim of this study was to compare the total excreta collection technique and comparative slaughter technique and estimate the lysine maintenance (Lysm) requirement in meat quail. For this purpose, were used 64 male meat quail, 45 days old, with initial weight of 173.93 ± 29.43g, distributed in completely randomized design, with four treatments (digestible lysine levels) and four replicates of four birds per cage, totaling 16 experimental units. The experimental diets were formulated using the "dilution" technique to provide increasing levels of digestible Lys, corresponding to 0.306; 0.442; 0.578 and 0.714%. To confirm that lysine was the first limiting nutrient in the experimental diets, a fifth diet (control) was used, obtained by adding 1.73 g/kg of L-lysine HCl (78.5%) to the diet containing 0.306% of digestible lysine, to reach a concentration of 0.442%. With that, there was the addition of four experimental units (16 birds). The experiment lasted 15 days and the light program adopted was 16 hours. Were evaluated: final weight (FW; g / bird); variation in weight (%); feed intake (FI; g / kg0.75.day-1); nitrogen intake (NI; g / kg0.75.day-1); digestible Lys intake (LysI; mg / kg0.75.day-1), nitrogen excretion (NE; g / kg0.75.day-1) and body nitrogen deposition (BND; mg / kg0.75.day-1). The data of each variable were subjected to normality and homoscedasticity tests, analysis of variance and the means were compared with the control treatment using the Dunnett test. The BND data (mg / kg0.75.day-1) obtained by the two techniques were regressed as a function of LysI (mg / kg0.75.day-1) through simple linear regression, with the maintenance coefficient defined as the LysI necessary for the BND to be equal to zero. To compare the equations obtained by the two techniques, a parallelism test was performed, using the technique as a categorical variable and LysI (mg / kg0.75.day-1) as a covariate. The recommendations obtained were converted and expressed in relation to the metabolic protein weight at maturity (CPm0,73 × u). The BND increased with the level of dietary Lys, and the more deficient diet provided BND lower than the control diet in both techniques. By means of simple linear regression of the BND (mg / kg0.75.day-1) as a function of LysI (mg / kg0.75.day-1) the Lysm were estimated at 17.08 mg / kg0.75.day-1 using the total excreta collection technique and 17.72 mg / kg kg0.75.day-1 using the comparative slaughter technique. By the parallelism test, there was no effect (P=0.2475) between the coefficients of the individual equations, so that only one equation was sufficient to describe the BND as a function of the LysI, with the Lysm being estimated at 17.32 mg / kg0.75.day-1. The total excreta collection and comparative slaughter techniques are equivalent and the Lysm in meat quails is 17.32 mg / kg0.75.day-1, corresponding to 26.84 mg / kg0.75.day-1or 56.34 mg / kgCP0.73.u.day1.